(untitled) - Sinha, Radha (Rome, 1984)
Contents: I. Introduction; II. Major characteristics and cause of landlessness; III. Economic and social conditions of the landless and other groups;... .
Keywords: Quyền sử dụng đất,Land tenure; Nước đang phát triển,Developing countries